Medicinal importance, pharmacological activities, and analytical aspects of hispidulin: A concise report - Kanika Patel; Dinesh Kumar Patel (Journal of Traditional and Complementary Medicine, 2017)
Herbal medicines have been played an important role in the human civilization since very ancient time as a food, cloth, medicine and other aspects. Some of the important drugs in the modern medicine were derived from the natural sources such as aspirin, digitalis, quinine, vincristine, vinblastine etc. Hispidulin (4′, 5, 7-trihydroxy-6-methoxyflavone) is a flavones derivative found in plant such as Grindelia argentina, Arrabidaea chica, Saussurea involucrate, Crossostephium chinense, Artemisia and Salvia species. Hispidulin have antioxidant, antifungal, anti-inflammatory, antimutagenic, and antineoplastic properties. So far, various analytical methods have been investigated and developed for detection of hispidulin in the plant materials. Productions of hispidulin through different tissue culture techniques have been also investigated. Present review summarized medicinal uses, pharmacological activities and analytical aspects of hispidulin. From the above mentioned aspects, we can conclude that, this review will be helpful to the researcher in the field of natural product for the development of novel molecule for the treatment of different disorders.